IMPLEMENTATION OF INTERESTED TIME WORKING AGREEMENTS AT PT.INDO MATRA POWER IN ACCORDANCE WITH LAW No. 13 of 2003 CONCERNING MANPOWER - Rantih Maeza Putri; Shenti Agustini (ConCEPt - Conference on Community Engagement Project, 2022)
PT Indo Matra Power is a company engaged in the field of Electricity, . PT Indo Matra Power can be said, a fairly large company with a fairly large number of employees, however PT Indo Matra Power does not enter into an employment agreement with its employees. Whereas the agreement between the company and the employee is a important. Therefore, the author wants to take this topic as a practical work report. In this practical work, the author forms a draft agreement unspecified working time. From this design, it is intended that PT Indo Matra Power and its workers have bonds and can fulfill each other's rights and obligations. With the draft work agreement already made, Entrepreneurs feel better understand what rights and obligations entrepreneurs have to do give, and if the worker violates the company rules the employer is more it's easy to give sanctions because it's already stated in the agreement work. Meanwhile, the workers feel that there is legal certainty from the parties involved workers with this work agreement starting from the rights and obligation must be fulfilled by workers and clarity in the calculation of overtime and clarity in calculating wages. At the time of implementation of the results of practical work that the author made did not exist obstacles, both from employers and from workers, but there are only a little criticism in calculating work overtime